2022
DOI: 10.1007/s40122-022-00443-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Methylprednisolone for Lung Surgery: a Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Introduction:The administration of methylprednisolone (MP) is a component of perioperative multimodal analgesia that mitigates the potentially deleterious effects of postoperative pain and opioid consumption. However, a systematic evaluation of the efficacy and safety of MP is lacking. The present systematic review and meta-analysis was performed to quantify the potential clinical benefits and risks of perioperative MP in lung surgery. Methods: We searched seven electronic databases for randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…However, the relationship between the use of steroids and an increased risk of infection remains unclear. According to the several meta-analyses, no signi cant difference was found in infection rates between the groups treated with systemic corticosteroids and those not treated with corticosteroids [34,35]. In addition, Grijalva et al showed that the risk of infection was associated with the dose of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between the use of steroids and an increased risk of infection remains unclear. According to the several meta-analyses, no signi cant difference was found in infection rates between the groups treated with systemic corticosteroids and those not treated with corticosteroids [34,35]. In addition, Grijalva et al showed that the risk of infection was associated with the dose of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently, there are no efficient drugs or therapies for LPS-induced ALI in clinical practice. A promising strategy to prevent and treat ALI is to suppress the excessive production of inflammatory cytokines through anti-inflammatory drugs, including corticosteroids, such as methylprednisolone [10], dexamethasone (DEX) [11], prednisolone [12]. However, the clinical application of corticosteroids is usually accompanied by various severe side effects, such as hyperglycemia, hypertension, hypokalemia, dyslipidemia, osteoporosis, myopathy and immunosuppression [13][14][15].…”
Section: Introductionmentioning
confidence: 99%